Analyzing outsourced software development in the downstream petroleum sector in Ghana - Blebo, Quist Sylvester Nii (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the Award Degree of Master of Science in Project Management.